2011
DOI: 10.1007/s00038-011-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Times to drink: cross-cultural variations in drinking in the rhythm of the week

Abstract: Objectives The time of drinking in terms of daytime versus evening and weekday versus weekend is charted for regular drinkers in 14 countries in Europe, Asia, Latin America, Africa and Oceania. Methods national or regional adult population surveys from the GENACIS project. Results: The weekly rhythm of drinking varies greatly between societies. Drinking was generally more likely after 5 pm and on weekends. To this extent, alcohol consumption is now regulated by a universal clock. The relation of time of day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…This is in line with a recent international study reporting that drinking frequency, but not the time of day, was related to alcohol problems [51]. We conclude that the ‘atypical' drinking patterns of drinking alone or to cope as well as absenteeism represent relevant early markers for the risk for developing an AUD, possibly not only in the context of BIHAs but also during any adolescent alcohol consumption.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with a recent international study reporting that drinking frequency, but not the time of day, was related to alcohol problems [51]. We conclude that the ‘atypical' drinking patterns of drinking alone or to cope as well as absenteeism represent relevant early markers for the risk for developing an AUD, possibly not only in the context of BIHAs but also during any adolescent alcohol consumption.…”
Section: Discussionsupporting
confidence: 91%
“…One aspect of human drinking patterns is high alcohol intake on consecutive days, especially on weekends [28]. The modified model used in this study, with alcohol access during three consecutive days followed by a deprivation period for four days was introduced to mimic human weekend consumption.…”
Section: Alcohol Intake Using Three Consecutive Days Of Intermittent mentioning
confidence: 99%
“…Most of the recent studies have been conducted in the North-American context, while some studies have shown that different countries have different attitudes and patterns of alcohol use (Kuntsche et al, 2006;Room et al, 2012). In Southern European countries, alcohol is often moderately consumed at mealtimes (Room & Mäkelä, 2010) whereas in other European countries people drink more for social reasons (Atwell et.…”
Section: Introductionmentioning
confidence: 99%